From Spiritual Vigilance to Tactical Ambush: A Socio-Cultural Recontextualization of Pesantren Ethos During the Second Military Aggression in Indonesia - Abdul Aziz, Faqih; Niam, Khoirun; Rozaqiy, Rohmat Robi'; Mutha'aliin, Ahmad Hikam; Miftahur R, Ziyad Ahmad (Islam Futura, 2026)
Conventional military historiography concerning the Second Dutch Military Aggression (1948–1949) frequently separates General Sudirman’s guerrilla strategy from the spiritual dimensions of its agents, reducing spirituality to a mere ideological motivator. This article bridges the theoretical gap between military historiography and the sociology of religion gap by examining the sociological mechanisms through which the pesantren ethos was recontextualized into effective combat strategies. Addressing the ambiguity of "spirituality" in strategic studies, this research dissects the transposition of Spiritual Vigilance (Muraqabah) and Ascetic Discipline (Riyadhoh) into military operations. Employing a socio-historical approach and Critical Discourse Analysis (CDA) on guerrilla memoirs and pesantren ethical literature, this study reveals that amidst the total collapse of state logistics, General Sudirman functioned as a cultural broker who transformed the santri habitus into a tactical methodology. The findings indicate two fundamental forms of recontextualization: (1) the Riyadhoh habitus was converted into extreme logistical resilience, and (2) Muraqabah was transformed into tactical stealth, a prerequisite for ambush tactics. This study concludes that Indonesian guerrilla effectiveness was the result of converting spiritual cultural capital into military capital. The theoretical implications underscore that in asymmetric warfare, religion evolves beyond jus ad bellum (motivation) into jus in bello (operational methodology)